Mobility Management and Resource Management of Internet of Vehicles in Converged Heterogeneous Network Scenario - Qiong Yang; Jing Hu; Weiwei Xia (Dianxin kexue)
According to characteristics of internet of vehicles in converged heterogeneous network scenario, mobility management and resource management were studied. The converged heterogeneous network scenario was analyzed based on the concepts of internet of things and internet of vehicles. Network architecture of internet of vehicles was proposed by research of communication equipments, communication mode and networking. Compared with general heterogeneous network, vehicles are moving quickly in internet of vehicles which leads to frequent handoff. In order to solve this problem, mobility management in internet of vehicles was studied. Various communication equipments and communication modes lead to various service requirements and resource management based on priority was proposed according to different priority services. In resource management of heterogeneous network, high priority service should have priority in resource allocation, access control and network selection.